Comparing the composition and bioactivity of Crataegus monogyna flowers and fruits used in folk medicine. - Barros, Lillian (2011)
Introduction- Studying local plant foods is of particular interest as they often contain high amounts of bioactive compounds. Furthermore, their nutritional and medicinal impact must be documented and supported with scientific studies. Crataegus monogyna is an example of “functional food” traditionally used all over South European countries. Objective- A complete chemical and bioactive characterization of flower buds, flowers, unripe, ripened and over ripened fruits was performed. Methodology- Chemical characterization included determination of proteins, fats, ash, and carbohydrates, particularly sugars by HPLC-RI, fatty acids by GC-FID, tocopherols by HPLC-fluorescence, phenolics, flavonoids, β-carotene and ascorbic acid, by spectrophotometric techniques. Bioactivity was evaluated through screening of antioxidant properties: radical scavenging effects, reducing power, and inhibition of lipid peroxidation. Results- Flowers revealed the highest tocopherols and ascorbic acid contents, as also the best n-6/n-3 fatty acids ratio. Over ripened fruits showed the highest levels of carbohydrates, sugars and SFA. Unripe fruits presented the highest PUFA contents with the best PUFA/SFA ratio, as also the highest levels of phenolics and the most promising antioxidant properties (EC50 < 20.83 µg/ml; even better than trolox). Conclusion- This study shows the potential of different parts of Crataegus monogyna as sources of several compounds, including nutrients and nutraceuticals. Moreover, it supports the documented nutritional and medicinal impact of this species.